2004
DOI: 10.1111/j.0269-8463.2004.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme sensitivity of biological function to temperature in Antarctic marine species

Abstract: Summary1. Biological capacities to respond to changing environments dictate success or failure of populations and species over time. The major environmental feature in this context is often temperature, and organisms across the planet vary widely in their capacity to cope with temperature variation. With very few exceptions, Antarctic marine species are more sensitive to temperature variation than marine groups elsewhere, having survivable temperature envelopes between 5 °C and 12 °C above the minimum sea temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
277
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 348 publications
(294 citation statements)
references
References 26 publications
10
277
2
5
Order By: Relevance
“…These turbulent and complex oceanographic processes increase heterogeneity in a system that may otherwise be considered highly stenothermal and stable (Barnes et al, 2006;Clarke et al, 2009). Small changes in temperature are known to cause drastic changes in metabolic rates of Antarctic benthic invertebrates in shallow water (Peck et al, 2002;Peck et al, 2004) but to date there is no published work on metabolic rates of deep-sea Antarctic invertebrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These turbulent and complex oceanographic processes increase heterogeneity in a system that may otherwise be considered highly stenothermal and stable (Barnes et al, 2006;Clarke et al, 2009). Small changes in temperature are known to cause drastic changes in metabolic rates of Antarctic benthic invertebrates in shallow water (Peck et al, 2002;Peck et al, 2004) but to date there is no published work on metabolic rates of deep-sea Antarctic invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Low temperatures increase the cost of calcification and reduce metabolic rates (Peck et al, 2004), and increasing temperatures have been shown to directly increase growth rates of Southern Ocean bivalves (Nolan and Clarke, 1993;Brey et al, 2011). The effect of temperature can also be observed with a decrease in shell thickness with latitude in buccinid gastropods and echinoids while increasing shell thickness in the bivalve genus Laternula (Watson et al, 2012), where mechanical damage and associated shell repair increases calcification (Harper et al, 2012) at the cost of increased metabolic activity (Phillip et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2°C (Peck 2002), they start to lose critical biological functions at temperatures 2-3°C higher than current summer maxima (Peck et al, 2004). The question posed is how do we monitor the effects of heat stress in such organisms and are heat shock proteins the most appropriate biomarker for environmental stress in the Antarctic?…”
Section: Introductionmentioning
confidence: 99%
“…Advection from the sub-Arctic into the Arctic in both the Pacific and Atlantic sectors provides potential pathways of dispersal for planktonic eggs and larvae and facilitates the expansion of fish populations into a warming Arctic (Hollowed et al, 2013). The advection of warmer waters into the Arctic, combined with local warming, suggests that boreal fish species may increasingly outcompete cold-adapted, stenothermic (requiring a narrow range of ambient temperatures) species (Peck et al, 2004;Laurel et al, 2016aLaurel et al, , 2016b, resulting in a ''borealization" of the Arctic (Fossheim et al, 2015). Significant changes in the advection of zooplankton or ichthyoplankton under climate warming would cause changes in the populations of fish.…”
Section: Effects Of Advective Changes On Fishmentioning
confidence: 99%